Improvement Coagulation Process in Removing Turbidity and Total Organic Carbon from Contaminated Water by Mixing Two Coagulants (University of Thi-Qar Journal for Engineering Sciences, 2023)
Turbidity previously linked with the presence of pathogens has been eradicated by the coagulation process. Coagulation is a chemical treatment procedure that removes solids from water by changing the electrostatic charges of particles suspended in water. The eradication of turbidity and total organic carbon (TOC) has been investigated in this research by adding coagulants such as alum and FeCl3 respectively in concentrations (0, 5, 15, 25, 35, 45mg/L)to water in each jar on a jar measure. And studying the effect of the coagulant concentration on the removal of turbidity and total organic carbon(TOC) .The concentration used (0,5,15,25,35 mg/L)in each jars in the jartest .The speed of flash and slow mixing got initially by testing with three different speeds (flash mixing 400,300,220rpm )and(slow mixing 50,60,70rpm) and then selecting the one that provided the least turbidity and total organic carbon. The same procedure done with three different pH of water (6,7.25,8 )to study the effect of pH on coagulation . The findings show that FeCl3 is more successful at removing turbidity and total organic carbon. It has been observed that 220 rpm,50 rpm,6 pH yields the best outcomes. Mixing of two Coagulant alum and FeCl3 was studied to improve coagulation process and reduce the cost of coagulant .Mixing of two coagulants was made with proportions (Alum100%+Fecl30%, Alum75%+Fecl325%, Alum50%+Fecl3 50%, Alum25%+Fecl375%, Alum0%+Fecl3100%). Best removal of turbidity and TOC at 25 mg/L (75 percent Alum25%+Fecl375%,).This study proved that Mixing coagulation improves the coagulation process in removing turbidity and total organic carbon .